Gestational age at diagnosis of early‐onset fetal growth restriction and impact on management and survival: a population‐based cohort study. (7th March 2017) - Monier, I; Ancel, P‐Y; Ego, A; Guellec, I; Jarreau, P‐H; Kaminski, M; Goffinet, F; Zeitlin, J; ,
Abstract : Objective: To investigate the impact of gestational age (GA) at diagnosis of fetal growth restriction (FGR) on obstetric management and rates of live birth and survival for very preterm infants with early‐onset FGR. Design: Population‐based cohort study. Setting: All maternity units in 25 French regions in 2011. Population: Fetuses diagnosed with FGR before 28 weeks of gestation among singleton births between 22 and 31 weeks of gestation without severe congenital anomalies. Methods: We studied the effects of GA at diagnosis on perinatal management and outcomes. We used multivariable regression to identify antenatal factors (maternal characteristics, ultrasound measurements and sex) associated with the probability of live birth. Main outcomes measures: Live birth and survival to discharge from neonatal care. Results: A total of 436 of 3698 fetuses were diagnosed with FGR before 28 weeks (11.8%); 66.9% were live born and 54.4% survived to discharge. 50% were live born when diagnosis occurred before 25 weeks, 66% at 25 weeks and >90% at 26 and 27 weeks of gestation. In all, 94.1% of live births were by prelabour caesarean, principally for maternal indications before 26 weeks. Low GA at diagnosis, an estimated fetal weight or abdominal circumference below the third centile and male sex were adversely associated with live birth in adjusted models. Conclusion: Gestational age at FGR diagnosis had an impact on the probability of live birth and survival, after consideration of other perinatal characteristics. Investigations of the outcomes of births with early‐onset FGR need to include stillbirths and information on the GA at which FGR is diagnosed. Tweetable abstract: Evaluations of active management of pregnancies with early onset growth restriction should include stillbirths. Tweetable abstract: Active management of pregnancies suspected with early fetal growth restriction is initiated at 26 weeks.